Dinâmica de expansão da silvicultura no estado de Goiás - Araújo, Lázaro Gabriel de Oliveira (2019)
Forestry, although it constitutes a strategic activity for the energy and transformation sector in the Brazilian economy, there are few efforts focused on the spatial modeling of the growth dynamics of planted forests, both locally and regionally. This study aims to know the spatial elements, as well as their degrees of influence on the conduction of the phenomenon of expansion of forestry in the state of Goiás, between 2000 and 2015. The work was divided in three parts: i) exploratory analysis, through a survey of spatially explicit variables directly linked to the conduction of the phenomenon; ii) elaboration and execution of the forestry expansion model for the state of Goiás between the years 2000 and 2015, using the Dinamica EGO platform; iii) construction of two prediction scenarios by 2030. The first scenario retains the weights of the variables according to the previously simulated expansion model; and the second one, reorders weights, seeking to induce greater allocative efficiency. The results show that the allocation of forest stands is strongly attracted to areas close to the road structure and to the consuming centers of wood products, such as refrigerators, bulk warehouses, and mining. Regarding the environmental characteristics, the occurrence of a great part of the plantations in areas with corrugated relief and profiling oriented to agriculture of medium technological level and low level of mechanization, besides the sprayed distribution in small areas, indicates that a considerable portion of producers opts for peripheral areas and little planning regarding productivity and quality of wood.